A comparative study on tumour response, intrathoracic symptom palliation and toxicities in locally advanced inoperable non-small cell lung cancer patients receiving palliative chemoradiation versus radiation alone - Panmei, Ruby; Sobita Devi, Yumkhaibam; Devi, Angom Ronibala; Swer, Dorafiona; Devi, Ningthoujam Dinita; Mahawar, Rahul (International Journal of Research in Medical Sciences, 2025)
Background: Locally advanced unresectable non-small cell lung cancer (LA-NSCLC) is a key focus in research, as it presents significant treatment challenges, with low survival rates despite progress in radiotherapy and systemic therapies. This study compares two palliative regimen for LA-NSCLC, one with radiation alone the other arm as concurrent chemoradiation therapy (CCRT) with nab-paclitaxel. Methods: A Randomised Controlled Trial was conducted in the Department of Radiation Oncology, Regional Institute of Medical Sciences, Imphal from July 2022 to June 2024. Sample size of 96 was calculated. In the Control Arm (Arm A), patients were treated with radiation alone at the dose of 36 Gy/12# and in the Study Arm (Arm B), CCRT was given at 40 Gy/20 with nab-paclitaxel given as a weekly dose. The primary endpoint is to see the tumour response, intrathoracic symptom palliation and treatment toxicities between the two arms. Secondary endpoints include progression-free survival (PFS). Results: Our study has a better overall response rate in Arm B compared to Arm A and the most effectively palliated symptoms in our study were chest pain and shortness of breath. Arm B exhibited more pronounced acute and late radiation toxicities which were manageable. The median PFS was 8 months in Arm A and 13 months in Arm B. Conclusions: Overall response rate after completion of treatment was higher in palliative concurrent chemoradiation group as compared to palliative radiation therapy group, but in totality, the two palliative lung cancer treatment regimens were almost equal in efficacy in terms of intrathoracic symptom palliation and toxicity.